Carbon accounting initiatives: Case study of a petroleum refinery in Malaysia to prepare for future carbon market - Amanda, H.L.C.; Mahmood, Noor Zalina; Abdul Raman, Abdul Aziz (2010)
Petroleum refining process produces a large amount of atmospheric pollutants including greenhouse gases which are attributed to global warming. The international community inevitably addressed the global warming issue by introducing a market-based mechanism known as Emission Trading Systems (ETS) under the Kyoto Protocol which imposes binding limits to developed nations using three flexibility mechanisms, including the Clean Development Mechanism (CDM).